Virtualization of Research Data Services during the COVID-19 Pandemic as an Opportunity to Enhance Research Data Support - Berenica Vejvoda; Rong Luo; Selinda Berg (International Journal of Librarianship (IJoL), 2021)
For Canadian academic libraries, the emergence of the COVID-19 pandemic necessitated an unprecedented switch to virtual services. An abrupt halt to in-person activities required almost all libraries to utilize new technologies in order to continue serving patrons. While the Academic Data Centre (ADC) has traditionally offered both physical and online services, with the emergence of the pandemic, the ADC pivoted to exclusively online service provision. Through new initiatives such as remote desktop access to statistical software, embedded virtual spaces for consultation and breakout discussions, online workshops and teaching, and the use of social media--the Academic Data Centre emerged successful in supporting student and faculty data needs.  While virtually scaling up data services was essential to avoid disrupting researchers working with data, the shift to online services also presented an unexpected opportunity to reflect meeting the data needs of users and, in turn, strategize innovative future data service delivery. Three themes emerged from our reflection: emphasis on greater accessibility; more flexible instruction; and the benefits for cultivating a data community. As emerge from the pandemic, the ADC expects to further embrace newly implemented technologies and virtual services to further scale and augment research data service support.